2016
DOI: 10.1002/alr.21879
|View full text |Cite
|
Sign up to set email alerts
|

The impact of endoscopic sinus surgery on paranasal physiology in simulated sinus cavities

Abstract: Surgery changes the geometry and physiology of the paranasal sinuses. These changes are likely to have an impact on wound healing, mucociliary function, and microbial ecology in postoperative cavities. Application of this model to further understand the effects of surgery may help to optimize surgical techniques and improve topical drug delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…It has been shown that the airflow into maxillary sinus was virtually zero before surgery (33,34) . However, after performing different sizes of virtual antrostomy, the airflow increased between 0.2% to 50.5%, depending on the antrostomy size.…”
Section: Thermal and Humidity Exchangementioning
confidence: 99%
“…It has been shown that the airflow into maxillary sinus was virtually zero before surgery (33,34) . However, after performing different sizes of virtual antrostomy, the airflow increased between 0.2% to 50.5%, depending on the antrostomy size.…”
Section: Thermal and Humidity Exchangementioning
confidence: 99%
“…Images are shown from a normal subject and from two subjects with chronic rhinosinusitis before (preop) and after (postop) endoscopic sinus surgery and after an endoscopic Lothrop procedure ( ELP ). (Reprinted with permission from Ref . Copyright 2016 Wiley)…”
Section: Computational Fluid Dynamics In the Pulmonary Systemmentioning
confidence: 99%
“…inside the sinus. These changes are likely to have an impact on mucociliary function and microbial ecology . Postsurgical subjects are an interesting group to investigate but whose CT‐images are not often available.…”
Section: Application Of Computational Fluid Dynamics In the Nosementioning
confidence: 99%
See 1 more Smart Citation
“…ESS can be used to reset the CRS with an altered bacterial population by opening the obstructed sinus ostium, thus allowing for mechanical disruption and drainage of the bacterial population, changing the physiology of the paranasal sinuses, and enabling better delivery of topical medications into the paranasal sinuses. In a computer simulation model by Jain et al., the effect of ESS on paranasal physiology and topical medication delivery was evaluated by comparing the preoperative and postoperative computed tomography (CT) images. The computer model demonstrated that with ESS, there would likely be a change in airflow, temperature, pressure, and water vapor in the operated sinuses.…”
mentioning
confidence: 99%